2001
DOI: 10.1007/s004640080146
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and the prevalence of trocar site herniation after laparoscopic fundoplication

Abstract: The prevalence of trocar site herniation after laparoscopic fundoplication was minimal at 3%. All hernias occurred at the midline supraumbilical port, the only site where open trocar insertion was employed. As a consequence of these observations, we have developed a new method of open trocar placement. This method utilizes a paramedian skin incision and separate fascial incisions through anterior and posterior rectus sheathes, with retraction of the rectus abdominis muscle laterally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
77
0
12

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 23 publications
4
77
0
12
Order By: Relevance
“…The same survey revealed that 86.3% of herniae occurred in sites where the trocar diameter was 10 mm or more, and umbilical herniae were found in 75.70% as compared to lateral hernias in 23.70% [2]. In another retrospective study of 320 cases, the prevalence of trocar site herniation after laparoscopic fundoplication was minimal at 3% [3]. All herniae occurred at the midline supraumbilical port [3].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The same survey revealed that 86.3% of herniae occurred in sites where the trocar diameter was 10 mm or more, and umbilical herniae were found in 75.70% as compared to lateral hernias in 23.70% [2]. In another retrospective study of 320 cases, the prevalence of trocar site herniation after laparoscopic fundoplication was minimal at 3% [3]. All herniae occurred at the midline supraumbilical port [3].…”
Section: Discussionmentioning
confidence: 94%
“…In another retrospective study of 320 cases, the prevalence of trocar site herniation after laparoscopic fundoplication was minimal at 3% [3]. All herniae occurred at the midline supraumbilical port [3].…”
Section: Discussionmentioning
confidence: 95%
“…However, incisional hernia can form post-operatively, a situation whereby contents of the abdominal cavity protrude through a weakness in the abdominal wall as a result of improper trocar site wound closure (commonly at the linea alba near the umbilicus [3][4][5]). Such cases have a prevalence of approximately 1-5% [6][7][8][9][10][11], meaning that, in the U.S alone, up to 100,000 cases of port site incisional hernia occur each year. This outlines a clear need for a more robust solution to the current methodology of wound closure in laparoscopic surgery.…”
Section: Introductionmentioning
confidence: 99%
“…
We enjoyed the recent report by D. J. Bowrey et al [1] about risk factors and the prevalence of trocar site herniation after laparoscopic fundoplication. As a consequence of their observations, they state that they have developed a new method of open trocar placement by use of a paramedian skin incision and separate fascial incisions with retraction of the rectus abdominus muscle laterally.

However, we have been using this technique, which we described in 1999 in this journal [2], since 1992 in laparoscopic fundoplications and in other laparoscopic procedures (more than 3000 procedures).

…”
mentioning
confidence: 96%
“…We enjoyed the recent report by D. J. Bowrey et al [1] about risk factors and the prevalence of trocar site herniation after laparoscopic fundoplication. As a consequence of their observations, they state that they have developed a new method of open trocar placement by use of a paramedian skin incision and separate fascial incisions with retraction of the rectus abdominus muscle laterally.…”
mentioning
confidence: 96%